2011
DOI: 10.1111/j.1475-6811.2011.01353.x
|View full text |Cite
|
Sign up to set email alerts
|

Relational uncertainty and cortisol responses to hurtful and supportive messages from a dating partner

Abstract: This paper evaluates theoretical claims linking relational uncertainty about a relationship partner to experiences of stress during interactions with that partner. Two observational studies were conducted to evaluate the association between relational uncertainty and salivary cortisol in the context of hurtful and supportive interactions. In Study 1, participants (N = 89) engaged in a conversation about core traits or values with a partner, who was trained to be hurtful. In Study 2, participants (N = 89) recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 83 publications
3
45
0
Order By: Relevance
“…However, research using the combined approach has documented divergent patterns of results for self uncertainty when controlling for partner and relationship uncertainty in the same model. Thus, to address these concerns, conducting and reporting results of both analytical strategies is suggested (Priem & Solomon, ; Solomon et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, research using the combined approach has documented divergent patterns of results for self uncertainty when controlling for partner and relationship uncertainty in the same model. Thus, to address these concerns, conducting and reporting results of both analytical strategies is suggested (Priem & Solomon, ; Solomon et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The disconfirming messages may exacerbate their beliefs that they are the source of the problem, increasing their anxiety and dissatisfaction with the relationship. For example, a series of studies by McLaren, Priem, and Solomon (McLaren & Solomon, ; McLaren, Solomon, & Priem, ; Priem, McLaren, & Solomon, ; Priem & Solomon, ) has shown that hurtful messages that are disconfirming are physiologically stressful and relationally distancing. Likewise, immediacy cues where a person appears to be distracted, uninvolved, and lacking in expected levels of intimacy are anxiety‐producing for support receivers (Guerrero et al, ).…”
Section: Verbal Rumination and Brooding Ruminationmentioning
confidence: 99%
“…The relational turbulence theory (Solomon, Knobloch, Theiss, & McLaren, ) posits that times of transition in relationships lead to tumultuous interactions and uncertainty about the future of the relationship. These processes (e.g., relational uncertainty during transitions) are associated with more depressive symptoms (Knobloch & Knobloch‐Fedders, ) and heightened stress, as evidenced by increases in cortisol (Priem & Solomon, ).…”
Section: Relational Turbulence and Inertia Theoriesmentioning
confidence: 99%